A new species of Blattisocius (Acari: Mesostigmata: Blattisociidae), with a new characterisation of the genus - Oliveira, Daniel C.; Chandrapatya, Angsumarn; Moraes, Gilberto J. De (Zootaxa, 2015)
A new species of Blattisocius Keegan, Blattisocius thaicocofloris n. sp., is described from Thailand from adult females and males, raising to 18 the number of species known in this genus. This is the first species of this genus described from flowers (of Cocos nucifera L.; Arecaceae), although two species, Blattisocius apis Basha & Yousef and Blattisocius apisassociae Chinniah & Mohanasundaram, were reported in association with honeybees, which could suggest an association with flowers. The new species requires updates to the diagnostic characteristics of the genus and recently published keys for generic identification of blattisociid subfamilies, blattisociine genera and Blattisocius species.